Elusive Employment: Understanding the Role of Disability and Rehabilitation in Post-conflict El Salvador - Blackmore, Charlotte; Boyce, William; Gallupe, Owen (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2009)
In the developing world, persons with disabilities tend to be concentrated in the poorest segments of society, in which they have limited access to education, training, and employment. When they do work, this is generally at a lower level than their true potential, and in temporary or unstable markets. In El Salvador, poor skill development, lack of awareness and neglect have further marginalized those with disabilities from contributing to the economic welfare of their families and communities.Using two pilot communities in El Salvador, this investigation highlights how the economic needs and challenges of persons with disabilities differ within rural and urban settings. Among individuals with disabilities residing in urban areas, discrimination and inaccessibility prevail as challenges in attaining employment, whereas a lack of training and skills is more commonly noted as a barrier to employment among respondents from rural areas.Although the economic barriers faced by persons with disabilities vary widely between communities, these differences have not been addressed by current rehabilitation models. This research provides guidance to local Salvadoran agencies in the development and implementation of needs-based rehabilitation programming at the community level.